APLIKASI PEMBERIAN KREDIT MIKRO PADA BANK XYZ DENGAN METODE ANALITYCAL HIERARCHY PROCESS - Astuti, Reny Wahyuning; Nurjani, Yeni; Susanti, Putri (FORTECH (Journal of Information Technology), 2017)
XYZ Bank is one of the financial institutions in Indonesia that provide financial services in the form of payments on credit / installments and has several procedures and requirements that must be met by prospective customers. As an effort to improve bank profitability and efficiency and effectiveness of work it is necessary to do proper financing management. One alternative financing solution is to use the  Decision Support System based applications that can provide creditworthiness decisions. The Decision Support System is built using Analytic Hierarchy Process (AHP) method, where this method that can solve the problem with the compound criteria and details, in a comprehensive framework of thinking with consideration of hierarchy process which then performed the calculation of weights for each of the criteria in determines credit eligibility. Based on the results of the test program shows that this decision support system has been able to determine the creditworthiness of customers well.